Musik über Stimmen: Vokalinterpretinnen und-interpreten der 1950er und 60er Jahre im Fokus hybrider Forschung - Krüger, Anne-May 1978- (Hofheim Wolke, 2022)
Performers have always had a decisive influence on the creation, performance practice, distribution and reception of compositions. This makes them central players in the creation of music, although musicology has only recently discovered them as a subject of research in their own right. With the singers Cathy Berberian and Carla Henius as well as the actor and vocal artist Roy Hart, this publication focuses on three performers from the immediate and wider environment of the Darmstadt Summer Course for New Music who influenced the vocal repertoire of their time in a particularly incisive way - whether due to their specific vocal abilities and working methods or as initiators and patrons. This repertoire often raises practical performance questions: How can compositions be interpreted that were created as vocal portraits of a singer or that could possibly only be realised vocally by a single person? What relevance does this historical repertoire have in the present day and how does it define the scope of interpretation? What can interpretation achieve - not as the servant of a supposed authorial authority or as a medium for clarifying research results, but as an independent epistemic technique? This volume thus aims to do two things: on the one hand, to shed light on specific historical contexts and the application of the insights generated from them in music research and music practice, and on the other hand, to illustrate music practice in its potential as a process for generating knowledge. Both aspects are united by the understanding of interpretation as a creative practice. (Translated with Deepl.com)
Voraussetzungen -- Carla Henius, Cathy Berberian und Roy Hart : drei vokale Fallbeispiele -- Interpretationen : Konklusionen -- Verzeichnis der Archive -- Abbildungsverzeichnis -- Literaturverzeichnis.
Includes bibliographical references (pages 525-542) and index.
Keywords: Henius, Carla; Berberian, Cathy -- 1925-1983; Hart, Roy -- 1926-1975; Music history; Singing; Musical interpretation; Music philosophy and esthetics